2022
DOI: 10.3389/fonc.2022.767859
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Intelectin-1 in Cancer

Abstract: BackgroundIntelectin (ITLN) is an adipokine with two homologs—ITLN1 and ITLN2—that has various physiological functions. Studies analyzing the relationship between ITLN and cancer are focused on ITLN1; the available literature on ITLN2 and cancer is limited. This review aims to evaluate the role of ITLN1 in cancer without imposing any inclusion criteria, to examine pro- and anticancer roles for ITLN1 and to discuss whether the relationship between ITLN and cancer is mediated by obesity.FindingsOverall, ITLN1 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Researchers suggested that the concentration of circulating omentin-1 may be a diagnostic marker for breast cancer. Currently, the mechanisms linking omentin-1 to tumor development remain unknown, but studies have indicated that omentin-1 affects the course of cancers with different localizations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggested that the concentration of circulating omentin-1 may be a diagnostic marker for breast cancer. Currently, the mechanisms linking omentin-1 to tumor development remain unknown, but studies have indicated that omentin-1 affects the course of cancers with different localizations [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that circulating ITLN1 concentrations differ between cancer patients and healthy individuals ( 8 11 ). Indeed, in our recent narrative review ( 12 ), we observed a difference in circulating ITLN1 levels when people with cancer were compared to healthy individuals. The difference was influenced by cancer type since patients with gastrointestinal and prostate cancer showed higher concentrations of circulating ITLN1, while individuals with breast, bladder, renal and gynaecological cancer expressed lower circulating ITLN1 levels.…”
Section: Introductionmentioning
confidence: 86%
“…( 20 ) examined the relationship between ITLN1 and cancer in a systematic review and observed that concentrations ranged from 2 to 1100 ng/ml. Whilst comprehensive, their review had some methodological weaknesses that we addressed in a previous study ( 12 ). In healthy people, Watanabe et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovarian cancer, omentin levels are reduced in patients diagnosed with neoplasia compared to patients with benign gynecological lesions and in healthy women, which may confirm that ovarian cancer cells are capable of downregulating this adipocytokine [ 268 , 271 , 272 ]. Moreover, as indicated by Au-Yeung et al [ 271 ], ovarian cancer cells can suppress ITLN1 expression in mesothelial cells in visceral adipose tissue for cancer cell proliferation and metastasis formation.…”
Section: Omentinmentioning
confidence: 99%